EXPERIENCE IN RESEARCHING STUDENTS' ASSESSMENT - Ikromova Sitora Akbarovna (Economics, management, and digital innovation in education: contemporary trends and approaches, 2025)
this article students knowledge mastery level study and assessment experience illuminated . In the study modern pedagogical approaches and assessment methods used is , the students knowledge to take to the process impact provider factors analysis Research​​ results based on effective teaching methods working exit according to recommendations given .